Ownership structure and the cost of debt: Evidence from the Chinese corporate bond market - Sris Chatterjee; Xian Gu; Iftekhar Hasan; Haitian Lu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
Drawing upon evidence from the Chinese corporate bond market, we study how ownership structure affects the cost of debt for firms. Our results show that state, institutional and foreign ownership formats reduce the cost of debt for firms. The benefits of state ownership are accentuated when the issuer is headquartered in a province with highly developed market institutions, operates in an industry less dominated by the state or during the period after the 2012 anti-corruption reforms. Institutional ownership provides the most benefits in environments with lower levels of marketization, especially for firms with low credit quality. Our evidence sheds light on the nexus of ownership and debt cost in a political economy where state and private firms face productivity and credit frictions. It is also illustrative of how the market environment interacts with corporate ownership in affecting the cost of bond issuance.
URN:NBN:fi:bof-201909201493
Keywords: G12; G18; G32; G34; 330; Government ownership; institutional holding; credit spreads; market forces